EFFECTS OF NETWORK EXTERNALITY ON STARTUP GROWTH IN THE CREATIVE INDUSTRIES - Rizky Wardhani; Vanya Zelia; Hasan Hasan; Nailah Putri Andini (Yayasan Adra Karima Hubbi, 2025)
The growth of startups, particularly in the creative industries, has been significantly influenced by various external factors. Among these, network externalities play a crucial role in shaping startup development. Network externalities refer to the phenomenon where the value of a product or service increases as more people use it, creating a positive feedback loop. Understanding how network externalities impact startup growth is essential for entrepreneurs, investors, and policymakers. This study investigates the effects of network externality on the growth of startups in the creative industries, focusing on how these externalities contribute to market expansion and innovation. The research aims to explore the relationship between network externalities and the scalability of creative startups. It examines how startups can leverage external networks, both digital and social, to enhance their visibility, collaboration opportunities, and customer base. The study adopts a mixed-methods approach, combining quantitative surveys of creative entrepreneurs with qualitative case studies of successful startups. Data was collected from 150 creative startups across various sectors, including digital media, design, and entertainment. The findings suggest that network externalities significantly accelerate startup growth, especially in digital platforms where user engagement creates momentum. Startups that effectively harness network externalities experience faster customer acquisition, higher brand recognition, and increased opportunities for collaboration.